Halotolerant bacterial endophyte Bacillus velezensis CBE mediates abiotic stress tolerance with minimal transcriptional modifications in Brachypodium distachyon - Abd El-Daim, Islam A.; Raynes, Gareth; Fernandez-Fuentes, Narcis; Hawkins, Sarah; Cookson, Alan; Farrar, Kerrie (Frontiers in Plant Science, 2025)
Nitrogen and water are the primary resources limiting agricultural production worldwide. We have demonstrated the ability of a novel halotolerant bacterial endophyte, Bacillus velezensis CBE, to induce osmotic stress tolerance in Brachypodium distachyon under nitrogen-deprived conditions. Additionally, we aimed to identify the molecular factors in plants that contribute to the beneficial effects induced by B. velezensis CBE in B. distachyon. To achieve this, we conducted transcriptomic profiling using RNA-seq on 18-day-old B. distachyon seedlings treated with B. velezensis CBE in the presence or absence of available nitrogen, with and without osmotic stress. These profiles were then compared to those obtained from B. distachyon treated with known plant growth-promoting bacterial strains, Azospirillum brasilense Cd and Azoarcus olearius DQS4, under the same growth conditions. We identified differentially expressed genes (DEGs) in response to the combinations of bacterial strains and stress treatments. Interestingly, only 73 transcripts showed significant differential expression in B. velezensis CBE-treated plants under stress conditions, compared to 1,078 DEGs in plants treated with A. brasilense Cd and 2,015 DEGs in A. olearius DQS4. Our findings suggest that the novel endophyte B. velezensis CBE mediates osmotic stress tolerance in B. distachyon through the fine-tuning of molecular mechanisms with minimal transcriptional modifications.